Identify and Ranking the Factors Affecting Optimal Marketing Services of Regional Information Center for Science and Technology - Hassan Moghaddaszadeh (تحقیقات کتابداری و اطلاع‌رسانی دانشگاهی, 2018)
Purpose: The main objective of the study was to identify and ranking the factors affecting optimal marketing services of Regional Information Center for Science and Technology. Methodology: Due to the nature of the study descriptive- survey method has been used. The populations of the study indicate all users of Regional Information Center for Science and Technology including 15825 persons that based on simple random sampling and with use of Krejcie and Morgan table, 380 persons were selected as the sample population. For data collection researcher made questionnaire consisting of 57 items has been used. For data analysis and hypotheses testing ANOVA test has been used with the help of SPSS 22 version. Findings: Based on the result of factor analysis and scores obtained, 9 factors identified that have influence on optimal marketing of Regional Information Center for Science and Technology. The identified factors were respectively: promotion, product, physical evidence, communications, price, infrastructure, accessibility, persons and location. Originality: Considering the importance of marketing services in libraries and information centers, and since there has not been and specific research on the marketing of Regional Information Center for Science and Technology services, the present research has necessary innovation and can find solutions for this center and similar centers.